Break bulk and cargo management - Rowbotham, J. Mark (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This book covers the subjects of break bulk cargo, general cargo and project cargo, and how these cargoes are shipped. It deals with the cargoes themselves, the vessels used for their carriage, and how the carriage is managed using the process of vessel chartering. Alongside these, it also covers offshore vessel management and how offshore supply vessels are used to carry cargoes to offshore oil & gas installations. Break bulk cargo covers a wide variety of cargoes, from project cargo to more varied cargoes carried on an ad hoc basis, often between ports that are not equipped for container traffic. It also covers the carriage of specific cargoes that cannot fit inside or are unsuitable for containers. This includes the carriage of cargoes for major projects, and cargoes for the offshore sector, which is an area which is covered in a specific section in the book concerning the use of offshore supply vessels. To date, only minor elements of shipping books cover this kind of trade, hence the need for a new book that specifically covers this subject. The focus of this book is providing expert insights and detailed explanations of the practical issues related to all aspects of break bulk and general cargo management. The book is written for legal practitioners, shipping managers, managers of project cargo, oil & gas companies, shipping professionals, charterers, shipbrokers, shippers and anybody else involved in ad hoc vessel chartering for the carriage of break bulk, general and project cargoes. It will also serve as a valuable resource for students of shipping"--
Introduction -- introduction to general cargo shipping -- Break bulk shipping -- The globalisation of break bulk -- Break bulk cargo -- Break bulk storage -- Incoterms 2010 & 2020 -- Bimco & the Baltic exchange -- Vessel ownership & chartering : whats in a contract? -- Chartering documentation -- Break bulk and charter party freight calculations -- Project cargo management -- Project cargo insurance -- Offshore supply vessel chartering.
OCLC-licensed vendor bibliographic record.
Keywords: Contracts, Maritime; TRANSPORTATION / Ships & Shipbuilding / General; BUSINESS & ECONOMICS / Industries / Transportation; Breakbulk shipping